Colistin-Resistant Enterobacteriaceae Isolated From Process Waters and Wastewater From German Poultry and Pig Slaughterhouses - Savin, Mykhailo; Bierbaum, Gabriele; Blau, Khald; Parcina, Marijo; Sib, Esther; Smalla, Kornelia; Schmithausen, Ricarda; Heinemann, Céline; Hammerl, Jens A.; Kreyenschmidt, Judith (Frontiers in Microbiology, 2020)
Due to the high prevalence of colistin-resistant Enterobacteriaceae in poultry and pigs, process waters and wastewater from slaughterhouses were considered as a hotspot for isolates carrying plasmid-encoded, mobilizable colistin resistances (mcr genes). Thus, questions on the effectiveness of wastewater treatment in in-house and municipal wastewater treatment plants (WWTPs) as well as on the diversity of the prevailing isolates, plasmid types and their transmissibility arise. Process waters and wastewater accruing in the delivery and unclean areas of two poultry and two pig slaughterhouses were screened for the presence of target colistin-resistant bacteria (i.e. Escherichia coli, Klebsiella spp., Enterobacter cloacae complex). In-house and municipal WWTPs including receiving waterbodies were investigated as well. Samples taken in the poultry slaughterhouses yielded the highest occurrence of target colistin-resistant Enterobacteriaceae (40.2%, 33/82), followed by municipal WWTPs (25.0%, 9/36) and pig slaughterhouses (14.9%, 10/67). Recovered isolates exhibited various resistance patterns. The resistance rates using epidemiological cut-off values were higher in comparison to those obtained with clinical breakpoints. Noteworthy, MCR-1-producing K. pneumoniae and E. coli were detected in scalding waters and preflooders of municipal WWTPs. A total of 70.8% (46/65) of E. coli and 20.6% (7/34) of K. pneumoniae isolates carried mcr-1 on a variety of transferable plasmids with incompatibility groups IncI1, IncHI2, IncX4, IncF and IncI2 ranging between 30 kb and 360 kb. The analyzed isolates carrying mcr-1 on transferable plasmids (n=53) exhibited a broad diversity, as they were assigned to 25 different XbaI profiles. Interestingly, in the majority of colistin-resistant mcr-negative E. coli and K. pneumoniae isolates non-synonymous polymorphisms in pmrAB were detected. Our findings demonstrated high occurrence of colistin-resistant E. coli and K. pneumoniae carrying mcr-1 on transferrable plasmids in poultry and pig slaughterhouses and indicate their dissemination into surface water.